Althusser as Reader of Gramsci - Morfino, Vittorio (Universidad de Costa Rica, 2020)
The article reconstructs the complex relation between Althusser and Gramsci. Considering both published and unpublished writings, the article argues that this relation is profoundly ambivalent: on the one hand, Gramsci is considered the sole precursor in the Marxist tradition who tried to think the superstructure, and particularly politics; on the other hand, he is the paradigm of a conception of temporality and politics from which Althusser wants to take distance.